Social Comparison Theory and Interpersonal Contact - Kiwan Park; Y. Jin Youn (Asia Marketing Journal (Online), 2018)
Incidental envy influences behavior in various domains. However, no research, to date, has investigated whether incidental envy influences interpersonal behavior toward others who are unrelated to the emergence of the emotion. That is, the literature is silent on how those who experience incidental envy engage in interpersonal contact and how this may affect consumers. In this paper, we address this question by investigating the influence of incidental envy on interpersonal contact with others of higher or lower status based on the social comparison theory. We demonstrate that incidental envy (versus a neutral emotion) motivates people to contact higher status others to facilitate upward assimilation (experiments 1 and 2). We also show that when competition (a situational factor that heightens the personal relevance of the interaction with the target) is involved, individuals who feel envy (versus a neutral emotion) are more likely to contact lower status others to engage in downward contrast (experiment 3). We conclude with a discussion of the practical implications of our findings.